The face of forgiveness : a pastoral theology of shame and redemption - Jamieson, Philip D. (Downers Grove, IL : InterVarsity Press, 2016)
Jesus tells Peter to forgive "not seven times, but seventy-seven times" (Matt 18:22), and the atoning work of Christ is at the center of Christian thought. Yet many followers of Christ often struggle with offering or receiving forgiveness. The Face of Forgiveness seeks to address this dilemma and present a way forward. Utilizing contemporary distinctions between shame and guilt, Philip Jamieson shows how traditional Western atonement models have frequently failed to deal adequately with the full extent of Christ's victory. Jesus Christ has answered both the problem of human guilt and shame. It is only in facing Christ that we find our sins forgiven and receive a new identity. The author concludes by offering several strategies to aid Christians in understanding and appropriating the fullness of God's loving and forgiving work.
Whatever happened to the forgiveness of sins? -- Covering our nakedness : healing through therapy -- Guilt and shame -- Opened eyes and downturned faces -- The shame of the cross -- "As one from whom others hide their faces . . ." -- Living before Christ's face.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Forgiveness of sin; Forgiveness -- Religious aspects -- Christianity; Shame -- Religious aspects -- Christianity; Forgiveness of sin; Forgiveness -- Religious aspects -- Christianity; Shame -- Religious aspects -- Christianity; RELIGION / Christian Theology / Soteriology; Electronic books